(untitled) - Oneda, S. (Singapore, 1991)
This book the authors hope to arouse interest in the approach to broken symmetry from a fresh point of view. The authors argue that spectrum generating symmetries still maintain asymptotic symmetry for physical (not virtual) particles. When combined with the symmetry related equal-time commutation relations which are derivable from fundamental Lagrangian, asymptotic symmetry then demands a close interplay among the masses, mixing parameters and coupling constants of physical particles. From this point of view, we may understand the success of the naive quark model, remarkable mass and mass-mixing angle relations in QCD and electroweak theory and even the presence of dynamical selection rules. The method may also give us a powerful tool for the study of new physics where fundamental Lagrangian is not yet known.
Keywords: Particles (Nuclear physics),Đối xứng tiệm cận (vật lý),Hạt ((vật lý hạt nhân),Asymptotic symmetry (Physics); Technique,Kỹ thuật